1997
DOI: 10.2337/diacare.20.4.614
|View full text |Cite|
|
Sign up to set email alerts
|

Cholesterol Lowering With Simvastatin Improves Prognosis of Diabetic Patients With Coronary Heart Disease: A subgroup analysis of the Scandinavian Simvastatin Survival Study (4S)

Abstract: A subgroup analysis of the Scandinavian Simvastatin Survival Study (4S) KALEVI PYORALA, MD TERJE R. PEDERSEN, MD JOHN KJEKSHUS, MD OLE FAERGEMAN, MD ANDERS G. OLSSON, MD GUDMUNDUR THORGEIRSSON, MD THE SCANDINAVIAN SIMVASTATIN SURVIVAL STUDY (4S) GROUP OBJECTIVE -To assess in diabetic patients with coronary heart disease (CHD) the effect of cholesterol lowering with simvastatin on mortality and the risk of CHD and other atherosclerotic events.RESEARCH DESIGN A N D METHODS -A post hoc subgroup analysis was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
486
3
19

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,439 publications
(535 citation statements)
references
References 8 publications
15
486
3
19
Order By: Relevance
“…For example, salt restriction, dietary approaches to stop hypertension (DASH), or alcohol restriction may lower systolic blood pressure (SBP) about 5-10 mm Hg on average, while drug combinations routinely lower SBP more than 10 mm Hg in many clinical trials. [10][11][12] Despite evidence that intensified therapy is usually needed to achieve and maintain evidence-based chronic disease care goals, a number of studies document high levels of clinical inertia in patients with diabetes or lipid disorders 13,14 and demonstrate that more active clinical management improves absolute glycated hemoglobin (A1c), low-density lipoprotein-cholesterol (LDL), and SBP control. 12,15 …”
Section: Prevalence and Cost Of Clinical Inertia Prevalencementioning
confidence: 99%
“…For example, salt restriction, dietary approaches to stop hypertension (DASH), or alcohol restriction may lower systolic blood pressure (SBP) about 5-10 mm Hg on average, while drug combinations routinely lower SBP more than 10 mm Hg in many clinical trials. [10][11][12] Despite evidence that intensified therapy is usually needed to achieve and maintain evidence-based chronic disease care goals, a number of studies document high levels of clinical inertia in patients with diabetes or lipid disorders 13,14 and demonstrate that more active clinical management improves absolute glycated hemoglobin (A1c), low-density lipoprotein-cholesterol (LDL), and SBP control. 12,15 …”
Section: Prevalence and Cost Of Clinical Inertia Prevalencementioning
confidence: 99%
“…The UKPDS demonstrated the importance of maintaining good glycaemic control for prevention of the development and progression of complications among patients with type 2 diabetes [44]. Clinical trials have shown that pharmacological treatment of hypertension [45][46][47] and cholesterol reduction with a statin therapy [42,43,[48][49][50] are efficient ways of preventing stroke and other cardiovascular events in patients with diabetes or impaired fasting glucose.…”
Section: Menmentioning
confidence: 99%
“…3-Hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase inhibitors, also known as statins, are commonly used for the treatment of dyslipidaemia. A number of large studies have demonstrated that statin therapy is associated with a reduction in cardiovascular events in people both with and without type 2 diabetes [6][7][8][9][10][11][12]. While a reduction in LDL-cholesterol was observed in many of these studies, it is now considered that statins also mediate pleiotropic antiatherogenic effects that are independent of their effects on lipoproteins, and that this action may contribute to their efficacy in reducing cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%